Cervical Cancer Screening Uptake Inequality - Mehdi Mirzaei-Alavijeh; Mahin Amini; Seyyed Nasrollah Hosseini; Shima Khashij; Farzad Jalilian (Journal of Holistic Nursing and Midwifery)
Introduction: Cervical cancer is a significant public health concern and has caused numerous unfortunate deaths. The Pap smear (PS) test is a widely-recognized and affordable screening technique used to detect cervical cancer at an early stage. Objective: This study aimed to investigate the inequality in cervical cancer screening uptake. Materials and Methods: This cross-sectional research was conducted on 774 married 30–37 women selected by multi-stage cluster sampling. They were living in Kermanshah City, Iran, in 2019. Their socioeconomic status was evaluated using the principal component analysis (PCA) and was shown by the index and curve of concentration of socioeconomic inequality in PS. The obtained data were analyzed using the chi-square, t-test, logistic regression, and compensation statistical tests. Results: The mean age of participants was 45.42±10.66 years. About 43.9% of women had education levels under a diploma. Also, 89.3% of women were married, and 58.1% had already done a PS test at least once. In addition, 26.5% of women had a regular PS test uptake. The concentration index for PS test uptake was 0.062 (P=0.115). Education level (OR=1.181, 95% CI; 1.022, 1.364, P=0.024) and a positive family history of cervical cancer (OR=3.591, 95% CI; 1.811, 7.120, P=0.001) had significant impacts on regular PS uptake. Conclusion: A person’s level of education and family history of cervical cancer were the most critical factors for getting regular PS test uptake. Furthermore, the concentration index showed that the frequency of PS test uptake was slightly higher in the rich group. Focusing interventions on less educated and disadvantaged women may provide useful insights to promote PS test uptake, thereby reducing inequalities. Moreover, using fear appeal strategies to promote PS test uptake may be beneficial.